Stylistic-Connotative Functions of Paraguayismin Juan Manuel Marcos’ novel «The Winter of Gunther» - Igor Protsenko (Ибероамериканские тетради)
The article is about the peculiarities of the linguistic units, typical for Paraguay, together with its forms of speech and its use in literature. A description and general classification of the paraguayisms from several points of view is made: formal classification (phonetic paraguayisms; grammatical (morphosyntactic); lexical (including idioms and turns of speech); as well as its semantic classification. The sociolinguistic aspect in the use of paraguayisms in the daily life of the Paraguayans and in the literature of the country is underlined. The maximum attention in the article is paid to the lexical units. It is mentioned that the peculiarities of the language of Paraguay can be explained by considering the fact that Paraguay is a bilingual country where both Spanish and Guarani are spoken alike. In this regard, Paraguay is the only country in the world where the aboriginal language is officially enacted as the national language in accordance with the Paraguayan Constitution. Another aim of this article is to pay attention to the functions of paraguayisms, that emerge in the novel entitled Gunter’s winter by Juan Manuel Marcos. This novel is a striking example of the new Postboom Latin American literary movement, and has been considered by notorious specialists as the main Paraguayan novel of the last four decades, as well as one of the ten most important books in the history of Paraguay, and it has been translated into more than 40 languages.